Optical Coherence Tomography in Glaucoma - Sathyan, P (J Curr Glaucoma Pract, 2012)
The optic disk and the RNFL are the principal sites of apparent glaucomatous damage which precedes glaucomatous visual field alterations. RNFL defects are known to precede detection of visual field defects by approximately 6 years. Accurate early detection and monitoring of ONH and RNFL defects has become the prime focus of effective management of glaucoma. Optical coherence tomography employs low-coherence interferometry to obtain cross-sectional images of the ocular tissues. This review attempts to critically analyse the applications of both, anterior and posterior segment OCT in glaucoma management.